2012
DOI: 10.5575/geosoc.2012.0011
|View full text |Cite
|
Sign up to set email alerts
|

Surface environments in the Japan Sea around the last glacial maximum

Abstract: Surface environments in the Japan Sea during the last glacial maximum (LGM: ka) are poorly constrained. Microfossil studies based on sediment core data (i.e., on changes in diatom, planktonic foraminifera, radiolaria, and calcareous nannofossil assemblages) indicate that sea surface temperatures (SSTs) during the LGM were much colder than those of today. Studies on the degree of unsaturation of alkenones in sediment cores suggest that SSTs during the LGM were -°C higher than present-day values. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…2020). During the LGM, in addition to cold water temperatures similar to current temperatures in the northern Sea of Japan of 46–48° N, low salinity (26–29) has been reported in the southern region of the Sea of Japan (Oba and Tanimura 2012). Although studies of salinity tolerance are lacking in E. bicyclis according to a few studies in the other kelp species, in general, kelps can grow within a salinity range of 26–29 (Bartsch et al.…”
Section: Discussionmentioning
confidence: 85%
“…2020). During the LGM, in addition to cold water temperatures similar to current temperatures in the northern Sea of Japan of 46–48° N, low salinity (26–29) has been reported in the southern region of the Sea of Japan (Oba and Tanimura 2012). Although studies of salinity tolerance are lacking in E. bicyclis according to a few studies in the other kelp species, in general, kelps can grow within a salinity range of 26–29 (Bartsch et al.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, the warm LGM SST was not supported by micropaleontological studies (Yokoyama et al., 2007). Records from diatom, benthic and planktonic foraminifera, and radiolarian species revealed that SST during the LGM was much lower than that of today (Hyun et al., 2013; Itaki et al., 2007; Koizumi & Yamamoto, 2011; Matsui et al., 1998; Nakagawa et al., 2003; Oba & Tanimura, 2012). Although the SST of the Japan Sea during the LGM remains controversial, we assumed that, supported by the above descriptions, the SST during the LGM was not higher than that in other periods.…”
Section: Introductionmentioning
confidence: 99%
“…Following this assumption, the abnormal reduction in δ 18 O there strongly suggests a low S JP event (S. Gorbarenko et al., 2021; E. Lee, Kim, & Nam, 2008; Matsui et al., 1998). However, partly because of the unclear relationship between δ 18 O and S JP , previous studies leave the exact value of minimum S JP during the LGM as disputable (28, Oba et al., 1991; 20, Tada, 1999; 29.8, S. A. Gorbarenko & Southon, 2000; 26–29, Oba & Tanimura, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The paleo Sea of Japan during the glacial low stand was mostly isolated from the North Pacific and received a continuous supply of freshwater from rivers and precipitation (Keigwin & Gorbarenko, 1992). Therefore, the seawater was stratified into two layers that were separated by a robust halocline, with less saline upper layer and a more saline lower layer (e.g., Gorbarenko & Southon, 2000;Lee, 2007;Matsui et al, 1998;Oba et al, 1991;Oba & Tanimura, 2012). The bottom deep-sea sediments deposited during this period had fine laminations, high sulfur content, and no benthic foraminifera, indicating that the halocline prevented the oxygen dissolved at the sea surface from diffusing into the deep layers (Crusius et al, 1999;Ishiwatari et al, 1994;Masuzawa & Kitano, 1984;Oba et al, 1991;Tada et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Stommel‐Arons model, the downward diffusion of heat should be compensated by the upward heat advection associated with upwelling from the lower layer, which occurred together with the deep convection at both polar seas. However, it is unlikely that the deep convection process reached the deepest layer of the paleo Sea of Japan during the LGM, because the less saline seawater occupying the upper stratum would prevent the surface water from becoming heavier than 23.2 σ t despite surface cooling (Oba & Tanimura, ). Moreover, the absence of microfossils below the depth of 500 m suggests the presence of a pycnocline (hence, oxycline), which would have prevented the surface water from diffusing downward (Ikehara et al, ; Itaki et al, ).…”
Section: Introductionmentioning
confidence: 99%